Dynamics of water evaporation in cold asphalt mixtures. (15th November 2017) - Saadoon, Tahseen; Garcia, Alvaro; Gómez-Meijide, Breixo
Abstract: Cold asphalt mixture (CAM) is a road materials obtained by mixing bitumen emulsion, aggregate, water and often cement at ambient temperature. It offers improved social, economic and environmental benefits compared to other paving materials, such as hot mix asphalt. However, its use as a structural layer is limited due to the weak mechanical performance it presents at early curing stages. This research aims to understand the dynamics of water evaporation in CAM, without and with cement additions and compare them to soil/granular materials without binder. With this purpose, dynamic water evaporation and hydraulic conductivity tests were carried out and the results were correlated to the mechanical performance through a semi-empirical model. Moreover, the pore size distribution index (n) for the different samples and its evolution over the drying time were estimated based on hydraulic conductivity tests. These results showed the relationship between the internal pore distribution and water dynamics during drying. In addition, it was seen that bitumen emulsion is the main component that delays the curing process of cold mix asphalt and the type and quantity of cement used in this research did not significantly help to accelerate it. The predictive model resulted accurate, fast and easy to use. Graphical abstract: Highlights: Pore size distribution of CAM changes during curing and affects the drying time. Bitumen emulsion is the component which produces greatest delays in drying of CAM. Type and quantity of added cement did not significantly affect the evaporation rate. A semi-empirical model was proposed to predict the mechanical performance of CAM.